Analisis Kualitas Air Tanah sebagai Air Baku Menggunakan Metode Scoring Struges di Tambak Sari Sidoarjo - Mochammad Adi Prasetyo; Faradlillah Saves (Portal: Jurnal Teknik Sipil, 2026)
Abstract — This study aims to evaluate the feasibility of shallow groundwater quality as a raw water source in Tambak Rejo Village, Waru District, Sidoarjo Regency. The study is motivated by indications of groundwater quality degradation, likely influenced by the proximity of wells to industrial wastewater discharge channels. A scoring method with the Sturges classification approach was applied to assess key chemical parameters, including pH, nitrate (NO₃⁻), nitrite (NO₂⁻), iron (Fe), and manganese (Mn), referring to the quality standards established by the Kementerian Kesehatan Republik Indonesia. Data were collected from six actively used dug wells. Water samples were analyzed in the laboratory and evaluated using a scoring method to determine groundwater feasibility. The results indicate that pH, nitrate, nitrite, and iron concentrations at all sampling points comply with the established standards. However, manganese (Mn) concentrations in three wells (wells 2, 3, and 6) exceed the permissible limits. Based on the scoring results, three wells are classified as feasible, while the remaining three are categorized as not feasible as raw water sources. In conclusion, groundwater quality in the study area has not fully met the required standards for raw water, primarily due to elevated manganese concentrations. Therefore, water treatment is necessary prior to use, along with improved environmental management to ensure sustainable groundwater quality.Keywords: Shallow groundwater, water quality, raw water, chemical parameters, Scoring Sturges, Sidoarjo.